2000
DOI: 10.1103/physreve.61.4310
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-enhanced folding and denaturation of globular proteins

Abstract: It is shown that microwave irradiation can affect the kinetics of the folding process of some globular proteins, especially ␤-lactoglobulin. At low temperature the folding from the cold denatured phase of the protein is enhanced, while at a higher temperature the denaturation of the protein from its folded state is enhanced. In the latter case, a negative temperature gradient is needed for the denaturation process, suggesting that the effects of the microwaves are nonthermal. This supports the notion that cohe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
121
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(130 citation statements)
references
References 12 publications
4
121
0
2
Order By: Relevance
“…There is currently no recognised biophysical basis for such non-thermal effects (Adair, 2002), although there have been suggestions that microwave fields might alter the rates of protein folding and unfolding (Bohr and Bohr, 2000;de Pomerai et al, 2003). This mechanism could plausibly explain the induction of a modest heat-shock response (de Pomerai et al 2000a, b;Leszczynski et al, 2002) via accumulation of partially unfolded proteins within cells.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently no recognised biophysical basis for such non-thermal effects (Adair, 2002), although there have been suggestions that microwave fields might alter the rates of protein folding and unfolding (Bohr and Bohr, 2000;de Pomerai et al, 2003). This mechanism could plausibly explain the induction of a modest heat-shock response (de Pomerai et al 2000a, b;Leszczynski et al, 2002) via accumulation of partially unfolded proteins within cells.…”
Section: Discussionmentioning
confidence: 99%
“…The thermal and non-thermal effects of RF have been recently explored in many biological systems (3)(4)(5), often yielding inconsistent or controversial results. Among the great deal of investigations raised in recent years, at least one evidence seemingly emerged, consisting in the fact that the use of mobile phones for 10 years or longer may increase the risk of certain types of cancer [odds ratio (OR), 1.18; 95% confidence interval (95% CI), 1.04-1.34], whereas this association was mostly insignificant for normal mobile phone users compared to non-users (OR =0.98; 95% CI, 0.89-1.07) (6).…”
Section: Introductionmentioning
confidence: 99%
“…Low-intensity 935 MHz radiation can affect microtubule proteins and suppress cell growth. Pacini et al (40) ) for up to 100 h. However, two independent groups of investigators demonstrated the capability of lowpower UHF radiation to induce reversible changes to cell protein structure, affect beta-lactoglobulin conformational changes, and stimulate the unfolding of citrate synthase (42)(43)(44). In addition, Leszczynski et al (45) found that mobile phone radiation changes the phosphorylation status of the heat shock protein-27, one of the stress family proteins.…”
Section: Cellular Biomarkers Of Rf/mw Exposurementioning
confidence: 99%